Peran Tambang Pasir terhadap Struktur Ekonomi Desa: Studi Ekonomi Pembangunan di Desa Gondoruso, Kecamatan Pasirian - Mohamad Helmi Wakhit Yansyah; Angela Clairine; Eithar Indah Dwi Lestari; Erica Natasha Wiyono (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Sand is the main commodity of the Gondoruso community, almost all levels of society feel the impact of the presence of sand mining. From sand, it can form a network ecosystem for local residents' livelihoods. Based on this phenomenon, researchers conducted an analysis using Max Weber's concept of Protestant Ethics and McLeland's need for achievement. Weber stated that the Protestant Ethics was the forerunner to the birth of the spirit of capitalism which brought human civilization to become the creature of capital it is today. This is in line with the thoughts of Mc Cleland who stated that to achieve progress in civilization, you need encouragement to achieve your goals. The need for achievement makes humans move to realize the progress of their civilization. This encouragement encourages people to think more rationally, ultimately encouraging capitalization to maximize existing potential. This research uses qualitative methods with an ethnographic approach. This is in line with analysis that attempts to describe and explain the reality that exists within a society.